Cidera Olahraga dalam Kaitannya dengan Spesifikasi Sepatu Olahraga - Kunjung Ashadi, ; Abdul Hafidz, (Kepelatihan Olahraga, 2009)
Sport dispute caused by many factors. One of them is sport equipment. Shoes as an item of sport equipment has contribution to prevent sport injuries or maybe, in bad effect, shoes exactly causes the happening of sport injuries. Unique and various characteristics of each sport branch are main factors to determine of design / making sport shoes.  Thats why each sport shoes uses various compotition materials, appropriate with each sport branch demand, to increase performance and absolutely minimize risk of sport dispute.